Artificial Intelligence and International Arbitration Law : Revolution or Evolution - Magdalena Łągiewska (Routledge, 2025)
The book asks whether the use of Artificial Intelligence (AI) and Generative AI (GenAI) in international arbitration represents a revolution or an evolution of the international dispute resolution landscape.Critically engaging with the transformative impact of the Fourth Industrial Revolution (4IR), this book focuses on the integration of AI and GenAI into international commercial arbitration. Set against the backdrop of rapid technological advancement, it explores how arbitral tribunals and stakeholders are cautiously yet progressively adopting these innovations in a manner that respects and preserves the foundational principles of arbitration. Through an interdisciplinary and practice-oriented approach, the book examines the evolving role of AI in arbitration. It analyzes how AI is perceived and applied by parties, arbitral institutions, and arbitrators, as well as assesses the legal frameworks in place to govern it. Offering a balanced analysis of both the opportunities and legal and ethical dilemmas posed by emerging technologies, the book asks if a duty of disclosure is relevant in relation to AI use, and what challenges this might entail. It also covers the status of AI-generated arbitral awards under international law, as well as copyright law.This book will be of interest to researchers in the field of international arbitration and commercial law.